Baccor, in vitro formation of biofilm in broken endodontic files in radicular canals (Research, Society and Development, 2022)
The aim of this study to evaluate the biofilm formation of sulfate-reducing bacteria from two microbial species, Desulfovibrio desulfuricans (oral and environmental strain) and Desulfovibrio fairfieldensis, in root canals with fractured endodontic files in vitro and the biocorrosive changes that these strains are capable of promoting on the metal surface of endodontic files. Fourteen teeth were included with fractured # 90 Kerr files and inoculants of Desulfovibrio desulfuricans strains and Desulfovibrio fairfieldensis in a modified Postgate E culture medium. The inoculated teeth were evaluated at 28, 41, 51 and 477 days. The biofilm was evaluated through scanning electron microscopy (SEM) and confocal laser scanning microscope with the fluorophore the Live / Dead® kit. For the 477 day, chemical pickling followed, with subsequent evaluation of the metallic surface of endodontic files in the SEM. In the biofilm analyzes of 28, 51 and 477 days, a mixed biofilm was observed, with a predominance of living cells and areas of corrosion along the entire metallic surface of the file for the last time, contrasting the metallic surface of the control groups. The SRB showed cellular activity both on the metal surface of the file and on the dentin surface of the root canal at the deepest levels of the root canal, apical and medium, promoting biocorrosion along the metal surface of endodontic files.